2008
DOI: 10.1021/bp049761m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Production Method and Gene Amplification on the Glycosylation Pattern of a Secreted Reporter Protein in CHO Cells

Abstract: We have investigated the independent effects of selective gene amplification (using the dhfr amplifiable selection marker) and culture operating strategy (batch vs repeated fed-batch vs semicontinuous perfusion) on the glycosylation of a recombinant reporter protein (secreted alkaline phosphatase, SEAP) produced in transfected Chinese hamster ovary (CHO) cells. HPLC analyses coupled with susceptibility to various exoglycosidases were used to determine the N-glycosylation profile of SEAP samples. The dhfr ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 34 publications
0
22
1
Order By: Relevance
“…This should be experimentally demonstrated by studying the effect of mannose concentration and culture temperature on mRNA stability and it is out of the scope of this work. An inverse relationship between l and productivity rate of other recombinant proteins has been observed for different cell lines in a variety of different cultures conditions (Lipscomb et al 2005). However, in disagreement with our results, Yokota and Tanji (2008) in CHO cells cultures under varied serum concentrations found a positive dependence between the l and the specific production rate of recombinant protein.…”
Section: Estimation Of Specific Ratescontrasting
confidence: 78%
“…This should be experimentally demonstrated by studying the effect of mannose concentration and culture temperature on mRNA stability and it is out of the scope of this work. An inverse relationship between l and productivity rate of other recombinant proteins has been observed for different cell lines in a variety of different cultures conditions (Lipscomb et al 2005). However, in disagreement with our results, Yokota and Tanji (2008) in CHO cells cultures under varied serum concentrations found a positive dependence between the l and the specific production rate of recombinant protein.…”
Section: Estimation Of Specific Ratescontrasting
confidence: 78%
“…Documented reports have shown that culture process variables can considerably affect the sialic acid levels of recombinant proteins [22,23]. A higher sialylation of biopharmaceutical proteins is advantageous because glycoproteins lacking terminal sialic acid are generally ineffective in vivo because of rapid clearance by asialoglycoprotein receptors [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is urgent to understand how cell culture conditions affect Neu5Gc levels. Extensive efforts have been made to describe the effects of environmental factors on the total sialic acid content of a glycoprotein [22,23]. However, there are very few literature reports describing the impact of culture conditions on glycoprotein Neu5Gc levels.…”
Section: Introductionmentioning
confidence: 99%
“…Cell growth and viability was measured on a Guava Benchtop Cytometer after staining with Viacount TM (Guava Technologies). SEAP activity was measured using the phosphatase assay as described previously (Lipscomb et al, 2005). Samples were diluted to ensure readings fell within the appropriate absorbance limits.…”
Section: Cell Lines and Transfectionmentioning
confidence: 99%